Clean Stove Initiative Forum Proceedings : Beijing, China, April 26-29, 2014 - World Bank (Washington, DC, 2015)
The objectives of the second EAP CSI Regional Forum are twofold. The first is to share the progress, findings, and challenges of implementing the initiative s second phase. The second is to promote South-South collaboration, learning, and knowledge-sharing, with a focus on China s experiences. The forum is being held in Beijing on April 28, 2014, as part of a four-day event (April 26 29, 2014). A two-day, pre-forum event held April 26 27 focuses on participation in the 8th China Clean Stoves Expo in Langfang, Hebei province. Post-forum, South-South knowledge-exchange activities, scheduled for April 29, feature a meeting with officials of China s Rural Energy and Environment Agency (REEA) on South- South collaboration, tour of the stove-testing center at China Agriculture University in Beijing, and field visits with local stove manufacturers in Gaobeidian, Hebei province. The forum is co-organized by the China Alliance for Clean Stoves (CACS) and the REEA, Ministry of Agriculture, with funding support provided by the Australian government s DFAT, through the World Bank s EAAIG, and ASTAE.